PENGARUH PEMBERIAN SAPONIN DENGAN DOSIS BERBEDA TERHADAP MORTALITAS IKAN KAKAP PUTIH (Lates calcalifer) - Hadi Pranggono; Tri Yusufi Mardiana; Nurul Afifah (Fakultas Perikanan Universitas Pekalongan, 2019)
ABSTRACT This study was conducted to determine the effect of saponin with different doses on mortality of white snapper (Lates calcalifer). The study was conducted on 18 to 31 July 2017 at the Center for Sea Aquaculture Development (BBPBL) Pesawaran District, Lampung. The experimental design used was Completely Randomized Design (RAL) with 4 treatments and 3 replications. The treatments included, treatment A (3 ppm), B treatment (5 ppm), C treatment (7 ppm), and D treatment (9 ppm). The results showed that administration of saponin with different doses gave a very significant effect on mortality of white snapper (F count> F table). The fastest time of death can be in treatment D (9 ppm) that is 45 minutes, followed by treatment of C (7 ppm) that is 74.6 minutes, then treatment B (5 ppm) is 91 minutes and longest time of death in treatment A ( 3 ppm) ie 128.6 minutes. The water quality of the research media is still feasible for the medium of snapper maintenance ie temperature 290 C, salinity 33 ppt, pH 7.82-8,10, DO 5,6-6,4, ammonia 0,11-0,13 ppm Keywords: White snapper, dose of saponin, mortality